Intrathecal Colistin and Intravenous Fosfomycin as a combination therapy for the treatment of Acinetobacter baumannii Ventriculitis and meningitis: a case report from Nepal - Khadka, Bikash; Poudel, Saroj (Nepal Journal of Neuroscience, 2021)
Treatment of central nervous system infection may be troublesome due to multi-drug resistance. Colistin is less successful as a treatment option due to poor CNS penetration when used intravenously. We present the successful management of a case with ventriculitis and meningitis due to MDR Acinetobacter baumannii species with the combined intraventricular administration of colistin and IV fosfomycin after the initial regimen of colistin given alone through both IVT and IV routes had failed.